3D transient numerical simulation of a helical roots air compressor for FCVs. (December 2021) - Wei, Huan; Xing, Linfen; Wang, Bingqi; Feng, Jianmei; Peng, Xueyuan
Oil-free helical Roots air compressors which have great application potential in air circulation systems for high-power fuel cell systems, such as commercial fuel cell vehicles (FCVs), have the advantages of active adaptation, low cost, large flow rate and high reliability. In this study, a three-dimensional transient numerical simulation model of a helical Roots air compressor was established by considering all leakage clearances. In this study, hexahedral structured dynamic grids were generated in the working chamber and the rotating angle was updated at an increment of 1° to ensure the mesh quality of the entire solving domain. The accuracy of the simulation model was validated using experimental data, and the maximum deviation was less than 4.0%. Based on the simulated results, the pressure field and variation of the pressure field with the rotation angle are presented. It shows that the pressure fluctuation at the discharge side was larger than that at the suction side. The influence of various leakage clearance on the volumetric efficiency was analyzed comparatively. Additionally, the flow field characteristic of clearance was revealed. It is found that the rotor tip clearance was the major factor for the reduction of volumetric efficiency when the size was larger than 0.12 mm instead of the interlobe clearance. It is suggested that more attention should be paid to control the clearance size to ensure the performance of helical Roots air compressors.